PENERAPAN ANALISIS COST VOLUME PROFIT (CVP) ANALYSIS PUNTUK PERENCANAAN LABA JANGKA PENDEK PADA TKIT AL FATHONY DEPOK - Budi Santoso; Khusnul Prasetyo; Tuti Binastuti (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
TKIT Al Fathony is a school located in Depok, West Java. In carrying out its activities for the last three years, TKIT Al Fathony has experienced a decrease in revenue until it suffers a loss in 2020. Facing this problem, TKIT Al Fathony needs to start doing good financial management and profit planning. Therefore the question in this study is about how the financial management at TKIT Al Fathony and how the profitability of TKIT Al Fathony by using Cost Volume Profit (CVP) analysis. The analytical method used in this research is to compare the budget and the realization of revenues and costs during 2021. In addition, it also uses CVP analysis to find out what the break even point and margin of safety are at TKIT Al Fathony. The results of the analysis show that in financial management, TKIT Al Fathony's financial planning is quite good, but in terms of controlling income and costs it is still weak. Profit calculation using CVP analysis produces almost the same profit as without using CVP analysis. So that the results of the calculation of the break even point and the margin of safety results can be applied at TKIT Al Fathony for profit planning.